Development of Energy-Efficient Routing Protocol in Wireless Sensor Networks Using Optimal Gradient Routing with On Demand Neighborhood Information - K. Nattar Kannan; B. Paramasivan (International Journal of Distributed Sensor Networks)
Wireless sensor networks (WSNs) consist of a number of autonomous sensor nodes which have limited battery power and computation capabilities with sensing of various physical and environmental conditions. In recent days, WSNs adequately need effective mechanisms for data forwarding to enhance the energy efficiency in networks. In WSNs, the optimization of energy consumption is a crucial issue for real-time application. Network topology of WSNs also is changed dynamically by anonymous nodes. Routing protocols play a major role in WSNs for maintaining the routes and for ensuring reliable communication. In this paper, on demand acquisitions of neighborhood information are used to find the optimal routing paths that reduce the message exchange overhead. It optimizes the number of hops for packet forwarding to the sink node which gives a better solution for energy consumption and delay. The proposed protocol combines the on demand multihop information based multipath routing (OMLRP) and the gradient-based network for achieving the optimal path which reduces energy consumption of sensor nodes. The proposed routing protocol provides the least deadline miss ratio which is most suitable to real-time data delivery. Simulation results show that the proposed routing protocol has achieved good performance with respect to the reduction in energy efficiency and deadline miss ratio.